Improvement of Preventive Maintenance Process Effectiveness in Insourcing and Outsourcing Scheme with House of Risk (HOR) Method Approach (A Case Study) - Budi Siswanto; Adithya Sudiarno; Putu Dana Karningsih; Henry Pariaman (IPTEK The Journal for Technology and Science, 2019)
Outsourcing has become the alternative scheme to gain improvement in several fields within a short time to many enterprises. One power generation in North Java implemented PM as planned maintenance strategy to maintain equipment by conducting insourcing and outsourcing scheme as PM execution. Both conditions must follow the same business process flow in PM execution process and there will occur some obstacles that interrupted PM process. The existing problem will be analyzed with House of Risk (HOR) method approach, supported by Integrated Manufacturing Open Systems Architecture (CIMOSA) process-based function modeling for identification method and Supply Chain Risk Identification System (SCRIS) risk structure identification used for mapping problem, root cause, and its relation. Analysis with HOR results in root causes that occurred within PM implementation process for both of them commonly has the same problem that is process business acknowledgment, but in outsourcing scheme not exist root cause on culture compliance and work task requirement, because they have a descriptive target to obtain service level agreement fulfillment. On both scheme still need an improving method to monitor and evaluate the PM work for better performance.